Assessment of the impact on time to complete medical record using an electronic medical record versus a paper record on emergency department patients: a study. Issue 12 (23rd August 2013) - Perry, Jeffrey J; Sutherland, Jane; Symington, Cheryl; Dorland, Katie; Mansour, Marlene; Stiell, Ian G
Abstract : Background: Electronic medical records are becoming an integral part of healthcare delivery. Objective: The goal of this study was to compare paper documentation versus electronic medical record for non-traumatic chest pain to determine differences in time for physicians to complete medical records using paper versus electronic mediums. We also assessed physician satisfaction with the electronic format. Methods: We conducted this before-after study in a single large tertiary care academic emergency department. In the 'Before Period', stopwatches determined the time for paper medical recording. In the 'After Period', a template-based electronic medical record was introduced and the time for electronic recording was measured. The time to record in the before and after periods were compared using a two-sided t test. We surveyed physicians to assess satisfaction. Results: We enrolled 100 non-traumatic patients with chest pain in the before period and 73 in the after period. The documentation time was longer using electronic charting, (9.6±5.9 min vs 6.1±2.5 min; p<0.001). 18 of 20 physicians participating in the after period completed surveys. Physicians were not satisfied with the electronic patient recording for non-traumatic chest pain. Conclusions: This is the first study that we are aware of which compared paper versus electronic medical records in the emergency department. Electronic recording took longer than paper records. Physicians were not satisfied using this electronic record. Given the time pressures on emergency physicians, a solution to minimise the charting time using electronic medical records must be found before widespread uptake of electronic charting will be possible.